Post-processing technology of perovskite illuminant and application thereof
By using post-treatment additives such as nitrate during the post-treatment process of perovskite luminescent, a passivation layer and collapsed the pores are solved, and the surface defects of perovskite luminescent in high temperature or light environment are improved, and its water oxygen stability and light stability are improved.
Patent Information
- Application Number
- CN202510024231.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-29
AI Technical Summary
Perovskite luminescents have surface defects in high temperature or light environments, resulting in a decrease in fluorescence intensity. It is difficult for existing high-temperature solid-state synthesis methods to take into account the stability of water, oxygen and light at the same time.
A specific post-treatment additive (such as nitrate) is used to mix it with the perovskite luminescent, and the post-treatment additive is diffused into the pores of the template agent during the heating process, forming a passivation layer and causing the pores to collapse, thereby improving the water oxygen stability and light stability of the perovskite luminescent.
Through post-treatment technology, perovskite luminescents can not only resist water, oxygen and heat, but also resist the generation of photoinduced defects, significantly improving their water oxygen stability and photostability.
Smart Images

Figure CN119899656A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of post-processing of perovskite quantum dots, and in particular relates to a post-processing technology of a perovskite luminescent body and an application thereof. Background Art
[0002] As a new type of luminescent material, metal halide perovskite (hereinafter referred to as perovskite) luminophore has the characteristics of excellent luminescence efficiency, narrow emission half-peak width, high color purity, adjustable visible light band, etc., and is simple to prepare, low cost, and easy to scale up production. It is expected to become a key luminescent layer material in the future display field and has broad application prospects in light-emitting diodes (LEDs), solar cells, lasers and other fields. However, since perovskite is a soft lattice ionic compound, high humidity, high temperature and strong light irradiation in the external environment can easily induce perovskite defects, thereby damaging its luminescence performance. Therefore, perovskite needs to meet the tests of water, oxygen stability and light stability at the same time.
[0003] High-temperature solid-state synthesis methods are often used to prepare perovskite luminophores, which have the advantages of being suitable for large-scale synthesis, high controllability, and simple processes. The existing high-temperature solid-state synthesis method is mainly divided into two steps: 1) mixing the perovskite precursor and the template; 2) calcining the precursor mixture, reacting and melting the perovskite precursor at high temperature, and supercooling and crystallizing in the template to form a perovskite luminophore. Due to the coating effect of the template, these perovskite luminophores can isolate water, oxygen, and external high temperatures, showing stability against water and high temperatures.
[0004] However, the template only has a coating effect and cannot effectively passivate the perovskite luminescent body. Therefore, the perovskite luminescent body still has a large number of surface defects. These defects will cause the fluorescence intensity of the perovskite luminescent body to decrease in a high temperature or light environment. If the surface defects of the perovskite luminescent body are passivated in the template pores, it is necessary to retain the pores used as the post-processing mass transfer path (see the Chinese patent CN118978913A previously applied by our company). However, the retention of the pores makes the template unable to completely block water and oxygen. It makes it impossible to take both water and oxygen stability and light stability into account at the same time, so it needs to be improved. Summary of the invention
[0005] The purpose of the present invention is to provide a post-treatment technology for perovskite luminescent bodies and its application, which can effectively passivate the perovskite surface by using specific post-treatment additives, and at the same time collapse the pores of the template agent, thereby simultaneously improving the water-oxygen stability and light stability of the perovskite luminescent body.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] A post-processing technology for a perovskite light emitting body comprises the following steps:
[0008] S1, mixing a perovskite luminescent body and a post-processing additive to obtain a mixed powder; the perovskite luminescent body includes a template and perovskite quantum dots located in the pores of the template, and the template has pores for a post-processing mass transfer path;
[0009] S2, placing the mixed powder into a reaction container and heating it, so that the post-treatment additive diffuses into the pores of the template to passivate the surface of the perovskite quantum dots, and at the same time, the post-treatment additive causes the pores of the template to collapse, thereby obtaining a fluorescent material encapsulating the perovskite quantum dots;
[0010] The perovskite quantum dots are lead halide perovskite quantum dots;
[0011] The post-treatment additive is a nitrate, wherein the nitrate is bonded to Pb to form a passivation layer, and the Pb comes from the lead halide perovskite quantum dots.
[0012] In the present application, the perovskite luminophore may be any perovskite quantum dot coated by a template in the prior art, and the pores of the silicon oxide have not collapsed or have not completely collapsed, so as to retain the pores as the post-processing mass transfer path. At the same time, it should be pointed out that the essence of this application is a technology for post-processing a substance (i.e., a perovskite luminophore) that has synthesized perovskite quantum dots in a template. For the preparation method of the perovskite luminophore, please refer to a perovskite nanocrystalline fluorescent material and its preparation method and application (publication number: CN118165723A) previously applied for and disclosed by our company, or other related methods disclosed in the prior art. At the same time, the present invention also provides the following methods as examples:
[0013] A method for preparing a perovskite luminescent body comprises the following steps:
[0014] Step 1: Grind and mix perovskite precursors such as cesium halide and lead halide and a template agent to obtain a mixture.
[0015] Step 2: Heat the mixture to allow the precursors to react in the template to form a perovskite emitter.
[0016] The above methods are merely examples and do not constitute a limitation on the method for preparing perovskite light emitters.
[0017] Furthermore, the post-treatment additive is Mg(NO 3 ) 2 , Zn(NO 3 ) 2 , Fe(NO 3 ) 3 , KNO 3 , NaNO 3 , Cu(NO 3 ) 2 , NH4 NO 3 , AgNO 3 , Ca(NO 3 ) 2 , Al(NO 3 ) 3 ,Ba(NO 3 ) 2 , Fe(NO 3 ) 2 At least one of .
[0018] Furthermore, the template is a microporous material and / or a mesoporous material;
[0019] The microporous material is one of microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride;
[0020] The mesoporous material is one of mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.
[0021] Furthermore, the lead halide perovskite quantum dots are APbX 3 structure;
[0022] Wherein, the A position is at least one of Cs, Rb, FA, MA, and GA;
[0023] X is one or both of Cl, Br or I.
[0024] Furthermore, the heating temperature in step S2 is in the range of higher than the melting point of the nitrate and lower than the thermal decomposition temperature of the nitrate.
[0025] Furthermore, the pore collapse of the template in step S2 includes complete collapse and partial collapse;
[0026] The heating temperature in step S2 is 100-400°C.
[0027] Furthermore, the PLQY of the fluorescent material encapsulating the perovskite quantum dots after soaking in water is ≥ the PLQY before soaking in water, and the PLQY of the fluorescent material encapsulating the perovskite quantum dots after soaking in water is ≥ the PLQY of the fluorescent material encapsulating the perovskite quantum dots after soaking in water, and the PLQY of the fluorescent material encapsulating the perovskite quantum dots after soaking in water is ≥ the 2 After continuous irradiation with blue light (450nm) for 100 hours, the luminescence intensity still maintained at least 80% of the initial intensity.
[0028] Furthermore, the mass ratio of the perovskite light emitter to the post-treatment additive in step S1 is (1-6):1.
[0029] Furthermore, the heating and heat preservation time of step S2 is at least 30 minutes. By limiting the heat preservation time, it is ensured that the pores with the template can absorb enough nitrate molten liquid.
[0030] An application of a perovskite luminescent body, wherein the perovskite luminescent body can be applied to a perovskite diffuser, inkjet printing, a wavelength conversion film, a quantum dot film or a Micro LED.
[0031] The beneficial effects of the present invention are mainly reflected in:
[0032] (1) The post-processing technology of this application is targeted at: Perovskite quantum dots that have been synthesized. At the same time, all the materials used in the post-processing process of this application are solid, which is suitable for the post-processing of quantum dots in the industrial scale-up stage. In other words, this application essentially provides a full solid-state Perovskite quantum dot post-processing technology.
[0033] (2) The present invention heats and melts the nitrate, and adsorbs it into the pores of the template. The nitrate ions bond with the Pb in the lead halide perovskite quantum dots in the pores to passivate the surface of the quantum dots. At the same time, the nitrate collapses the pores to achieve the technical effect of closing the pores of the template after passivation, thereby achieving the purpose of improving the stability of solid-state quantum dots. The perovskite luminescent body can not only resist water, oxygen, and heat, but also resist the generation of photoinduced defects, thereby simultaneously improving the water and oxygen stability and light stability of the perovskite luminescent body. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The XRD test pattern of the sample obtained in Example 1 of the present invention;
[0035] Figure 2 The spectrum of the sample obtained in Example 1 of the present invention;
[0036] Figure 3 The spectrum of the sample obtained for Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] Embodiment 1:
[0039] This embodiment provides a post-processing technology for a perovskite light emitting body, comprising the following steps:
[0040] Step 1: Grind and mix 1.064 g of cesium halide, 1.835 g of lead halide and 3.2 g of template MCM-41 molecular sieve for 2 h.
[0041] Step 2: Heat the mixed powder of step 1 to 450°C and maintain for 60 minutes, then cool naturally to obtain a perovskite light emitter.
[0042] Step 3: Weigh 500 mg of the perovskite luminescent material obtained after calcination in step 2, add 0.15 g of Al(NO 3 ) 3 , grind and mix.
[0043] Step 4: Take the perovskite light-emitting body obtained after grinding in step 3, place it in a reactor and heat it to 130 degrees Celsius, maintain it for 120 minutes and then cool it down naturally.
[0044] In the above, the cesium halide is cesium bromide; and the lead halide is lead bromide.
[0045] Experimental analysis: Take the powder obtained by sintering as above and test XRD; see Figure 1 The XRD pattern of the sample shows that the post-treated perovskite emitter forms Pb(NO 3 ) 2 .
[0046] The powder obtained by the sintering was tested for fluorescence quantum yield (PLQY), as shown in Table 1. The PLQY of the sample before soaking in water was 76%, and the PLQY after soaking in water was 76%. Compared with Comparative Example 1, the improvement of PLQY before soaking in water shows that the post-treatment technology of the present invention can passivate the perovskite CsPbBr 3 Defects of the luminescent body. The PLQY of the perovskite luminescent body without post-treatment decreased significantly after soaking in water, while the PLQY of the perovskite luminescent body after post-treatment remained almost unchanged after soaking in water, indicating that post-treatment can cause the pores to collapse and close.
[0047] The stability of the perovskite luminescent material obtained by the above post-treatment was tested under strong blue light irradiation environment. See Table 1 for details. 2 After continuous irradiation with blue light (450nm) for 100 hours, the luminous intensity of the luminescent body can maintain 87% of the original intensity. In contrast, the luminous intensity of the perovskite luminescent body provided in Comparative Example 1 without post-treatment under the same blue light test conditions dropped to 29% of the initial intensity after 100 hours. The blue light stability proves that post-treatment is beneficial to improve the stability of CsPbBr 3 Photostability of luminophores.
[0048] Embodiment 2:
[0049] This embodiment provides a post-processing technology for a perovskite light emitting body, comprising the following steps:
[0050] Step 1: Grind and mix 1.064 g of cesium halide, 1.835 g of lead halide and 3.2 g of template MCM-41 molecular sieve for 2 h.
[0051] Step 2: Heat the mixed powder of step 1 to 450°C and maintain for 60 minutes, then cool naturally to obtain a perovskite light emitter.
[0052] Step 3: Weigh 500 mg of the perovskite luminescent material obtained after calcination in step 2, add 0.15 g of Fe(NO 3 ) 3 , grind and mix.
[0053] Step 4: Take the perovskite light-emitting body obtained after grinding in step 3, place it in a reactor and heat it to 130 degrees Celsius, maintain it for 120 minutes and then cool it down naturally.
[0054] In the above, the cesium halide is cesium bromide; and the lead halide is lead bromide.
[0055] Experimental analysis: The powder obtained by sintering was tested for fluorescence quantum yield (PLQY), as shown in Table 1. The PLQY of the sample before soaking in water was 80%, and the PLQY after soaking in water was 81%. Compared with Comparative Example 1, the improvement of PLQY before soaking in water indicates that post-treatment can passivate the perovskite CsPbBr 3 Defects of the luminescent body. The PLQY of the perovskite luminescent body that has not been post-treated is significantly reduced after being soaked in water, while the PLQY of the perovskite luminescent body that has been post-treated is almost unchanged after being soaked in water, indicating that the post-treatment can cause the pores to collapse and close. In addition, it should be noted that the PLQY of 81% after soaking in water in this embodiment is slightly greater than 80% before soaking in water. This change is due to the measurement error of the detection equipment and the rounding error when rounding the data, so it can be considered as a reasonable fluctuation range in data analysis.
[0056] The stability of the perovskite luminescent material obtained by the above post-treatment was tested under strong blue light irradiation environment. See Table 1 for details. 2 After continuous irradiation with blue light (450nm) for 100 hours, the luminous intensity of the luminescent body can maintain 86% of the original intensity. In contrast, the luminous intensity of the perovskite luminescent body provided in Comparative Example 1 without post-treatment under the same blue light test conditions dropped to 29% of the initial intensity after 100 hours. The blue light stability proves that post-treatment is beneficial to improve the stability of CsPbBr 3 Photostability of luminophores.
[0057] Comparative Example 1:
[0058] This comparative example provides a post-processing technology for a perovskite light emitting body, comprising the following steps:
[0059] Step 1: Grind and mix 1.064 g of cesium halide, 1.835 g of lead halide and 3.2 g of template MCM-41 molecular sieve for 2 h.
[0060] Step 2: Heat the mixed powder of step 1 to 450°C and maintain for 60 minutes, then cool naturally to obtain a perovskite light emitter.
[0061] In the above, the cesium halide is cesium bromide; and the lead halide is lead bromide.
[0062] Experimental analysis: The powder obtained by the above sintering was taken to test the fluorescence quantum yield (PLQY), as shown in Table 1. The PLQY of the sample before soaking in water was 28%, and the PLQY after soaking in water was 20%.
[0063] The stability of the perovskite luminescent material obtained above was tested under strong blue light irradiation. See Table 1 for details. 2 After continuous irradiation with blue light (450nm) for 100 hours, the luminous intensity of the luminescent body can maintain 29% of the original intensity.
[0064] Table 1 shows the PLQY test results of the samples obtained in Examples 1-2 of the present invention and Comparative Example 1 and the ratio of the luminous intensity tested after 100 hours of blue light aging to the initial intensity.
[0065]
[0066] Table 1
[0067] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A post-processing technology for a perovskite light emitter, characterized in that: The steps include: S1, mixing a perovskite luminescent body and a post-processing additive to obtain a mixed powder; the perovskite luminescent body includes a template and perovskite quantum dots located in the pores of the template, and the template has pores for a post-processing mass transfer path; S2, placing the mixed powder into a reaction container and heating it, so that the post-treatment additive diffuses into the pores of the template to passivate the surface of the perovskite quantum dots, and at the same time, the post-treatment additive causes the pores of the template to collapse, thereby obtaining a fluorescent material encapsulating the perovskite quantum dots; The perovskite quantum dots are lead halide perovskite quantum dots; The post-treatment additive is a nitrate, wherein the nitrate is bonded to Pb to form a passivation layer, and the Pb comes from the lead halide perovskite quantum dots.
2. A post-processing technology for a perovskite light emitter according to claim 1, characterized in that: The post-treatment additive is at least one of Mg(NO3)2, Zn(NO3)2, Fe(NO3)3, KNO3, NaNO3, Cu(NO3)2, NH4NO3, AgNO3, Ca(NO3)2, Al(NO3)3, Ba(NO3)2, and Fe(NO3)2.
3. The post-processing technology of a perovskite light emitter according to claim 1, characterized in that: The template is a microporous material and / or a mesoporous material; The microporous material is one of microporous molecular sieve, microporous silica, microporous titanium dioxide, microporous alumina, microporous transition metal oxide, microporous sulfide, microporous silicate, microporous aluminate or microporous transition metal nitride; The mesoporous material is one of mesoporous molecular sieve, mesoporous silica, mesoporous titania, mesoporous alumina, mesoporous carbon, mesoporous transition metal oxide, mesoporous sulfide, mesoporous silicate, mesoporous aluminate or mesoporous transition metal nitride.
4. The post-processing technology of a perovskite light emitter according to claim 1, characterized in that: The lead halide perovskite quantum dots are of APbX3 structure; Wherein, the A position is at least one of Cs, Rb, FA, MA, and GA; X is one or both of Cl, Br or I.
5. The post-processing technology of a perovskite light emitter according to claim 1, characterized in that: The heating temperature in step S2 is in the range of higher than the melting point of the nitrate and lower than the thermal decomposition temperature of the nitrate.
6. A post-processing technology for a perovskite light emitter according to claim 5, characterized in that: The pore collapse of the template in step S2 includes complete collapse and partial collapse; The heating temperature in step S2 is 100-400°C.
7. The post-processing technology of a perovskite light emitter according to claim 1, characterized in that: The PLQY of the fluorescent material encapsulating the perovskite quantum dots after soaking in water is ≥ the PLQY before soaking in water, and the ... of the fluorescent material encapsulating the perovskite quantum 2 After continuous irradiation with blue light (450nm) for 100 hours, the luminescence intensity still maintained at least 80% of the initial intensity.
8. The post-processing technology of a perovskite light emitter according to claim 1, characterized in that: The mass ratio of the perovskite light emitter to the post-treatment additive in step S1 is (1-6):
1.
9. The post-processing technology of a perovskite light emitter according to claim 1, characterized in that: The heating and heat preservation time of step S2 is at least 30 minutes.
10. The use of a perovskite light emitting body according to any one of claims 1 to 9, characterized in that: The perovskite luminescent body can be applied to a perovskite diffuser, inkjet printing, a wavelength conversion film, a quantum dot film or a Micro LED.
Citation Information
Patent Citations
Perovskite nanocrystalline fluorescent material and preparation method and application thereof
CN118165723A
All-solid-state post-processing technology of perovskite quantum dots and application of all-solid-state post-processing technology
CN118978913A